Bis(diethylenetriamine)cadmium(II) diiodide - Huang, Bei (International Union of Crystallography, 2008)
In the title compound, [Cd(dien)(2)]I(2), where dien = diethylenetriamine (C(4)H(13)N(3)), the Cd(II) ion is in a distorted octahedral coordination environment. In the crystal structure, intermolecular N—H⋯I hydrogen bonds link cations and anions into a three-dimensional network.